Comparison of two statistical wave models for fatigue and fracture analysis of ship structures. (1st September 2019) - De Gracia, Luis; Wang, Helong; Mao, Wengang; Osawa, Naoki; Rychlik, Igor; Storhaug, Gaute
Abstract: Ocean crossing ship structures are continuously suffering from wave loads when sailing at sea. The wave loads cause large variation of structural stresses, leading to fatigue accumulation in ship structures. For the fatigue life prediction of ship structures, it is important to obtain both the long-term distribution and the time history of wave-induced loads. An essential step is to get reliable wave statistics and accurate description of the stochastic nature of sea state along a ship's sailing routes during her service time. Generally, the wave statistics are provided by the classification societies as a joint probability of significant wave height and mean wave period, also known as wave scatter diagram. In addition, different statistical wave models have been developed to describe wave environments along arbitrary shipping routes based on different data sources, e.g., hindcast data, satellite measurements, buoys, etc. In this paper, two statistical wave models based on hindcast data and satellite wave measurements are briefly introduced and compared with the wave measurements carried out by onboard radar. Both of the wave models are then used to generate the wave environments along given shipping routes. The effectiveness of the wave models is demonstrated by comparing the stochastic nature and the statistical characteristics of simulated sea state histories with those of the source oceanographic data. Finally, an application of the wave model to the fatigue assessment is presented. Highlights: Two statistical wave models are compared and validated by a ship's actual encountered wave conditions. Statistics of H s and stresses generated from the two models agree well with that from hindcast and onboard measurements. The fatigue and fracture analysis based on the two models agree well with that estimated from the measured stresses. The two models can also give variations of fatigue damage accumulated during various years' sailing. The capability of the two models for fatigue assessment is confirmed through the comparison with the onboard measurement.